Characteristics of Educational Management Based on Humanistic Philosophy - Rahmi, Eka; Kristiawan, Muhammad (Journal of Innovation in Teaching and Instructional Media, 2024)
Humanism is known to appear in the Latin vocabulary humanus which has the meaning of human morals or following the nature of a human being. In terms of terminology, humanism means the position and position of every human being based on the efforts possessed by humans in generating their natural abilities in body and spirit. Data collection techniques use information from various sources which will later be used as references and references from several sources like article, journal and books. Humanistic learning theory globally explains that the learning process involves physical and spiritual in order to optimize the process of change in learning. Education in this learning theory seeks various insights from the environment as a series of character making equally. The target of this theory is to focus on behaviors that are given the right to choose in determining the fate of the individual himself and being able to account for it in the future. The role of education is simply to create the best conditions by encouraging, inspiring, digesting, and empowering. Child-centered learning should be a key principle. They need to be most active, most experiential, and most learning- experienced. The success of school management depends on the implementation of this MPMBS.